Practical Considerations of PRN Medicines Management: An Integrative Systematic Review - Mardani, Abbas; Paal, Piret; Weck, Christiane; Jamshed, Shazia; Vaismoradi, Mojtaba (Frontiers in Pharmacology, 2022)
Background and objectives: Highly widespread use of pro re nata (PRN) medicines in various healthcare settings is a potential area for improper medication prescription and administration leading to patient harm. This study aimed to summarize and integrate the findings of all relevant individual studies regarding the practical considerations of PRN medicines management including strategies and interventions by healthcare professionals for safe prescription, dispensing, administration, monitoring, and deprescription of PRN medicines in healthcare settings. Methods: An integrative systematic review on international databases were performed. Electronic databases including Web of Knowledge, Scopus, PubMed (including MEDLINE), and Cinahl were searched to retrieve articles published until end of May 2021. Original qualitative, quantitative, and mixed methods studies written in English were included with a focus on PRN medicines management in healthcare settings. Research synthesis using the narrative method was performed to summarise the results of included studies. Results: Thirty-one studies on PRN medicines in healthcare settings by different healthcare providers were included after the screening of the databases based on eligibility criteria. They were published from 1987 to 2021. The majority of studies were from Australia, the United States, Canada, and the United Kingdom and were conducted in psychiatric settings. Given variations in their purposes, methods, and outcomes, the research synthesis was conducted narratively based on diversities and similarities in findings. Eight categories were developed by the authors as follows: “PRN indications and precautionary measures,” “requirements of PRN prescription,” “interventions for PRN administration,” “monitoring and follow up interventions,” “deprescription strategies,” “healthcare professionals’ role,” “participation of patients and families,” and “multidisciplinary collaboration.” Each category consists of several items and describes what factors should be considered by healthcare professionals for PRN medicines management. Conclusion: The review findings provide insights on the practical considerations of PRN medicines management in clinical practice. The suggested list of considerations in our review can be used by healthcare professionals for optimal PRN medicines management and safeguarding patient care.